2011
DOI: 10.1111/j.1945-1474.2010.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Ambulatory Care and Avoidable Hospitalizations at the Veteran Health Administration

Abstract: This paper explores the link between utilization of ambulatory care and the likelihood of rehospitalization for an avoidable reason in veterans served by the Veteran Health Administration (VA). The analysis used administrative data containing healthcare utilization and patient characteristics stored at the national VA data warehouse, the Corporate Franchise Data Center. The study sample consisted of 284 veterans residing in Florida who had been hospitalized at least once for an avoidable reason. A bivariate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…These findings may be used to influence enrollment in MFH programs. Although reductions in avoidable hospitalizations through enhanced access to primary care have been demonstrated previously, 2,4,8,13 the present results are particularly noteworthy because the MFH population is considered "more medically complex and disabled." Furthermore, a companion study focusing primarily on hospitalization but also the comparative effectiveness of the MFH program found that "incidents of adverse medical care resulting in hospitalization were less prevalent among MFH than CLC residents," whereas "no differences between the groups were observed for adverse drug events, falls or other injuries.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…These findings may be used to influence enrollment in MFH programs. Although reductions in avoidable hospitalizations through enhanced access to primary care have been demonstrated previously, 2,4,8,13 the present results are particularly noteworthy because the MFH population is considered "more medically complex and disabled." Furthermore, a companion study focusing primarily on hospitalization but also the comparative effectiveness of the MFH program found that "incidents of adverse medical care resulting in hospitalization were less prevalent among MFH than CLC residents," whereas "no differences between the groups were observed for adverse drug events, falls or other injuries.…”
Section: Discussionmentioning
confidence: 57%
“…This variable tends to be uncorrelated with the health outcome in question but significantly affects the frequency at which care is sought. 4 However, in the present analysis, concerns related to this potential bias are alleviated somewhat by the intertemporal differences across the ACSCs. In particular, the most significant (both statistically and practically) differences were recorded for CHF (57%) and COPD (54%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations